The L-type Ca2+ Channel Blocker Nifedipine Inhibits Mycelial Growth, Sporulation, and Virulence of Phytophthora capsici - Liu, Peiqing; Gong, Jie; Ding, Xueling; Jiang, Yue; Chen, Guoliang; Li, Benjin; Weng, Qiyong; Chen, Qinghe (Frontiers in Microbiology, 2016)
The oomycete vegetable pathogen Phytophthora capsici causes significant losses of important vegetable crops worldwide. Calcium and other plant nutrients have been used in disease management of oomycete pathogens. Calcium homeostasis and signalling is essential for numerous biological processes, and Ca2+ channel blockers prevent excessive Ca2+ influx into the fungal cell. However, it is not known whether voltage-gated Ca2+ channel blockers improve control over oomycete pathogens. In the present study, we compared the inhibitory effects of CaCl2 and the extracellular Ca2+ chelator EDTA on mycelial growth and found that calcium assimilation plays a key role in P. capsici mycelial growth. Next, we involved the voltage-gated Ca2+ channel blockers verapamil (VP) and nifedipine (NFD) to analyse the effect of Ca2+ channel blockers on mycelial growth and sporulation; the results suggested that NFD, but not VP, caused significant inhibition. Ion rescue in an NFD-induced inhibition assay suggested that NFD-induced inhibition is calcium-dependent. In addition, NFD increased P. capsici sensitivity to H2O2 in a calcium-dependent manner, and extracellular calcium rescued it. Furthermore, NFD inhibited the virulence and gene expression related to its pathogenicity. These results suggest that NFD inhibits mycelial growth, sporulation, and virulence of P. capsici.